Dual role of injectable curcumin-loaded microgels for efficient repair of osteoarthritic cartilage injury - Sun, Qicai; Yin, Wei; Ru, Xuanliang; Liu, Chun; Song, Baishan; Qian, Zhigang (Frontiers in Bioengineering and Biotechnology, 2022)
Curcumin has been widely used for the treatment of age-associated diseases, and showed chondroprotective potential for post-traumatic osteoarthritis (OA). However, due to the irregular-shaped and large-sized defects on joint cartilage in degenerated OA, the in vivo delivery and therapeutic effect of curcumin for effective repair remain challenging. In this study, we first present a PEG-GelMA [Poly(Ethylene Glycol) Dimethacrylate-Gelatin Methacrylate, PGMs] hydrogel microgel-based curcumin delivery system for both improved anti-inflammatory and pro-regenerative effects in treatment for cartilage defects. The curcumin-loaded PGMs were produced by a microfluidic system based on light-induced gelation of gelatin methacrylate (GelMA). This PGMs embedding curcumin at a relative low dosage were demonstrated to promote the proliferation and chondrogenic differentiation of mesenchymal stem cells in vitro. More importantly, the PGMs were shown to attenuate the inflammatory response of chondrocytes under IL-1β stimulation. Lastly, the in vivo application of the injectable PGMs significantly promoted the repair of large-sized cartilage injury. These results confirmed that curcumin-loaded PGMs can not only enhance the chondroprotective efficacy under inflammatory conditions but also induce efficient cartilage regeneration. This study provides an advanced strategy with anti-inflammatory and pro-regenerative dual-role therapeutic for treatment of extensive cartilage injuries.